1995
DOI: 10.1183/09031936.95.08010078
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide responsiveness in COPD patients with and without chronic hypercapnia

Abstract: C Ca ar rb bo on n d di io ox xi id de e r re es sp po on ns si iv ve en ne es ss s i in n C CO OP PD D p pa at ti ie en nt ts s w wi it th h a an nd d w wi it th ho ou ut t c ch hr ro on ni ic c h hy yp pe er rc ca ap pn ni ia a G. Scano*, A. Spinelli*, R. Duranti*, M. Gorini**, F. Gigliotti**, P. Goti*, J. Milic-Emili † Carbon dioxide responsiveness in COPD patients with and without chronic hypercapnia. G. Scano, A. Spinelli, R. Duranti, M. Gorini, F. Gigliotti, P. Goti, J. Milic-Emili. ©ERS Journals Ltd 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 34 publications
5
41
0
Order By: Relevance
“…Patients approaching the fatigue threshold usually adopt breathing strategies which reduce the chance of this highly deleterious state occurring. Initial observations in stable patients showed that their respiratory drive, as assessed by mouth occlusion pressure, was high but that there was a difference in the breathing pattern of patients who showed a high CO 2 tension when stable and those that did not [18]. The former tended to exhibit a more rapid shallow breathing pattern and this was investigated subsequently by workers in Italy who found that the tidal volume was inversely related to CO 2 tension as was the maximum pleural pressure that the subjects could develop [19].…”
Section: Physiological Basis Of Respiratory Therapy In Chronic Obstrumentioning
confidence: 99%
“…Patients approaching the fatigue threshold usually adopt breathing strategies which reduce the chance of this highly deleterious state occurring. Initial observations in stable patients showed that their respiratory drive, as assessed by mouth occlusion pressure, was high but that there was a difference in the breathing pattern of patients who showed a high CO 2 tension when stable and those that did not [18]. The former tended to exhibit a more rapid shallow breathing pattern and this was investigated subsequently by workers in Italy who found that the tidal volume was inversely related to CO 2 tension as was the maximum pleural pressure that the subjects could develop [19].…”
Section: Physiological Basis Of Respiratory Therapy In Chronic Obstrumentioning
confidence: 99%
“…The patient then underwent a carbon dioxide rebreathing test following standard technique [15]. During resting breathing and carbon dioxide (CO 2 ) rebreathing, P0.1 was recorded every 10 -20 s [5]. After a rest period of ¢20 min, CO 2 rebreathing was repeated.…”
Section: Study Protocolmentioning
confidence: 99%
“…An inability to maintain a normal respiratory motor response during an exacerbation of COPD could lead to critical hypoventilation, respiratory failure, and death. Unfortunately, investigations have yielded inconsistent results, with reports of increased [4], decreased [5,6], and equivalent [7,8] respiratory motor output in hypercapnic and normocapnic patients. These conflicting findings stem, in part, from limitations of techniques used to measure respiratory motor output, such as the diaphragmatic electromyogram and airway occlusion pressure [9].…”
mentioning
confidence: 99%
“…Surprisingly the authors do not discuss the findings of SCANO et al [2] in the same patients and address the very same problem, using the same CO 2 -rebreathing experiments. Their results showed that the response of the electrical activity in the diaphragm to hypercapnia was not significantly different in normocapnic and hypercapnic COPD patients or in control subjects.…”
mentioning
confidence: 88%